Education and development in Africa: lessons of the past 50 years for beyond 2015 - McGrath, Simon (2012)
As we move to discuss the nature of development targets post 2015, it is timely to consider what lessons can be learnt from 50 years of experiences of attempts to link education and development in Africa. This paper offers a historical account of key themes in African education and development and raises questions particularly about who sets targets and priorities and for whom.